Tamizaje fitoquímico y actividad antibacteriana de los extractos de Dryopteris filix-mas frente a Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium y Klebsiella pneumoniae - Paima Roque, Windy Katrina Hildaura (2025)
The objective of this study was to analyze the chemical composition and evaluate the antibacterial activity of ethanolic and chloroform extracts of leaves and rhizomes of Dryopteris filix-mas against different bacteria: Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 15442, Salmonella typhimurium ATCC 14028 and Klebsiella pneumoniae ATCC 10541. The samples were collected for convenience and processed to obtain the extracts, the antibacterial activity was evaluated using the agar disk diffusion technique (Kirby-Bauer) and macrodilution, determining the minimum inhibitory and bactericidal concentration (MIC-MBC). The results of this study confirmed the presence of important bioactive compounds such as phenols/tannins, lactones, saponins, flavonoids and catechins. Regarding antibacterial activity, the ethanolic rhizome extract stood out with moderate activity against S. typhimurium, with inhibition zones greater than 15 mm and an MIC of 7.81 mg/mL, classifying it as moderately active. Likewise, S. aureus showed susceptibility to the ethanolic rhizome extract, with an MIC of 3.9 mg/mL, classifying the extract as active. The study concludes that, although D. filix-mas contains various phytochemicals with bioactive potential, its antibacterial effect is limited and bacteriostatic in nature, since it only inhibited the growth of some strains without eliminating them. These findings highlight the need for additional research to determine its potential therapeutic application.